Assessment of the feed additive consisting of Lentilactobacillus buchneri (formerly Lactobacillus buchneri) DSM 16774 for all animal species for the renewal of its authorisation (Lactosan GmbH & Co.KG). (9th July 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Lentilactobacillus buchneri (formerly Lactobacillus buchneri ) DSM 16774 as a technological additive to improve ensiling of forage for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. There is no evidence that would lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concludes that the additive remains safe for all animal species, consumer and the environment under the authorised conditions of use. Regarding user safety Lentilactobacillus buchneri DSM 16774 is not irritant to skin and eyes but is considered a skin and respiratory sensitiser. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.